Study on the influence of biomechanical factors on emotional resonance of participants in red cultural experience activities - Huawei, Liang; Xiumei, Bi (Paladyn (Warsaw), 2025)
As an important part of Chinese culture, red culture has a profound historical heritage and rich spiritual connotations. The red culture experience aims to inspire participants’ patriotic feelings and national pride by recreating historic and revolutionary scenes and sharing stories of the revolution. To further enhance the impact of red cultural experience activities, this paper employs a minimum spanning tree (MST) analysis to investigate the emotional effects of eye and brain movement features on participants in these activities. A multimodal physiological signal emotion recognition model was constructed using EEG and eye movement data, and the accuracy of emotion classification for happy, sad, fearful, and neutral emotions was investigated. The research results show that the emotion recognition effect is optimal when eye movement, differential entropy feature, and MST attribute are integrated simultaneously. The three can achieve effective integration between EEG signals and eye movement signals across modes to obtain more emotion-related information and fully utilise the complementarity between this multimodal information.